Narration interactive ludique : les jeunes lecteurs se réapproprient la culture populaire sous forme de persona-fictions - France Vachey (Strenae)
By creating a fiction of his life, man has evolved within a phantasmatic in-between place, where he builds a narrative identity that allows him to become present to himself. Within the framework of a role-playing forum, where day after day he writes narrated events involving imaginary characters based on popular literary narratives, and embodies an imagined life through the narratives, a kind of fictional persona emerges as a subject in the making, wishing to reveal his character’s psychology to himself and others, as well as to proceed in his story, integrate events, and, through all of this, construct an identity.